Therapeutic Effect of Statins and LPS Antibody on Proinflammatory Mediator and Biochemical Markers of Sepsis Rat Model Induced by E. coli - Dian Samudra1,2, Sumarno Reto Prawiro3 , Sanarto Santoso3 , Aswoco A. Asmoro4 , Husnul Khotimah5 , A (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study aims to determine the effect of statins and LPS antibodies administration combined with E. coli intraperitoneal injection toward proinflammatory mediators (TNF-?, hs-CRP, PCT, and MDA) urea, BUN, and creatinine) and liver function (SGPT, SGOT, and total bilirubin) in sepsis rats. This study used 30 male white rats (Rattus novergicus strain Wistar) divided into 6 groups induced by E. coli bacteria combined with statins, LPS antibody (Ab-LPS), and a combination of statins+Ab-LPS. Examination of proinflammatory mediators (TNF-?, hs-CRP, PCT, and MDA) was carried out by the ELISA method through the examination of biochemical markers namely renal function (urea, BUN, and creatinine) and liver function (SGPT, SGOT, and total bilirubin) were analyzed by using the autoanalyzer. The data obtained were statistically analyzed using the T-test. The result shows that E. coli+statins gave significant changes on the MDA level at 0th hour administration and TNF-? and hs-CRP at 3rd hour administration. The E. coli+Ab-LPS treatment showed significant changes at the 0th hour administration for MDA, creatinine, and total bilirubin and at the 3rd hour administration for MDA. The E. coli+statins+Ab-LPS treatment showed significant changes in MDA, creatinine, and total bilirubin at 0th hour administration and on creatinine and total bilirubin at 3rd hour administration.